ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI RENTANG WAKTU PUBLIKASI LAPORAN KEUANGAN AUDITAN - Wijaya, I Gede Kurniawan; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2017)
The problem formulated in this study is whether the size of the company, the audit opinion and the audit committee impact on timescales publication audited financial statements. The purpose of this study was to determine the effect of firm size, audit opinion and the audit committee impact on timescales publication audited financial statements. The population used in this study are all manufacturing companies listed on the Stock Exchange period 2009-2014. By using purposive sampling in the selection of the sample, obtained a total of 18 companies were selected as sample, so that the total number of samples with 6-year study period was 108 samples. Tests in this study using multiple regression analysis. Hypothesis testing results show that the size of the company's significant negative effect on the financial publication time span. While the audit opinion and the audit committee have no effect on the time span financial publications. In addition, the size of the company, the audit opinion and the audit committee simultaneously affect the span of the publication of the audited financial statements.
Keywords: Time Range Publications Financial Reports, Company Size, Opinion, The Committee